Effects of dietary copper on elemental balance, plasma minerals and serum biochemical parameters of growing-furring male mink (Mustela vison) - Wu, Xuezhuang (Anim Nutr, 2015)
The objectives of this study were to study the effects of different levels of dietary copper on copper and zinc balance, plasma minerals and serum biochemical parameters of mink in the growing-furring periods. One hundred and five standard dark male mink were randomly assigned to seven groups with the following dietary treatments: basal diet with no supplemental Cu (Control); basal diet supplemented with either 6, 12, 24, 48, 96, or 192 mg/kg Cu from copper sulfate, respectively. The average daily gain (ADG) linearly (P = 0.0026, P = 0.0006) responded to increasing levels of Cu; maximal growth was seen in the Cu24 group. Feed efficiency tended to improve with the increase of dietary copper level (linear P = 0.0010, quad, P = 0.0011). Fecal copper, urinary copper, retention copper responded in a linear (P < 0.05) fashion with increasing level of Cu. The effect of level of Cu was linear (P < 0.001) for plasma Cu concentration. The serum glutamic-oxalacetic transaminase (GOT) and glutamic-pyruvic transaminase (GPT) activities were increased linearly (P < 0.05) with dose of Cu, but serum total protein (TP) and albumin (ALB) concentrations decreased linearly (P < 0.05) as dietary copper levels increased. Effect of level of Cu was linear (P < 0.001) for serum ceruloplasmin (CER) concentration or Cu-Zn superoxide dismutase (Cu-Zn SOD) activity. Supplemental dose of Cu linearly decreased serum triglyceride (TG) (P = 0.011) and total cholesterol (TC) (P = 0.007). Our results indicated that the activity of Cu-dependent enzymes was enhanced by increasing dietary Cu concentration and that supplementation of Cu in the diet of mink could alter the plasma lipid profile and copper concentration.